2019
DOI: 10.26486/jele.v5i1.949
|View full text |Cite
|
Sign up to set email alerts
|

Efl undergraduate students’ self-regulation in thesis writing: help-seeking and motivation-regulation

Abstract: Type Undergraduate thesis writing necessitates EFL students to self-regulate themselves, particularly in overcoming the difficulties they encounter and maintaining their motivation. To date, there has been little research on EFL undergraduate students’ self-regulation, help-seeking, and motivation-regulation in thesis writing, especially in Asian context. Under explanatory mixed-method framework, this research aimed to investigate how Indonesian EFL undergraduate students self-regulated their thesis writing pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 31 publications
2
34
1
Order By: Relevance
“…This finding indicates most graduate students are capable of repeating similar academic writing success if they have been exposed to this kind of positive learning nuance in their past time. This fourth finding is corresponding with the previous finding discovered by (Mbato & Cendra, 2019). They found that undergraduate students' motivation in thesis writing will be nourished consistently if meaningful and continuous supports are always given by their thesis advisors.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This finding indicates most graduate students are capable of repeating similar academic writing success if they have been exposed to this kind of positive learning nuance in their past time. This fourth finding is corresponding with the previous finding discovered by (Mbato & Cendra, 2019). They found that undergraduate students' motivation in thesis writing will be nourished consistently if meaningful and continuous supports are always given by their thesis advisors.…”
Section: Resultssupporting
confidence: 89%
“…It is worth restating here that there are seven current studies of academic writing conducted around the globe. The first study was conducted by (Mbato & Cendra, 2019). They discovered that self-regulated EFL learners can accomplish their undergraduate thesis writing since they have known how to seek help from others and maintain their learning motivation continuously.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, little research has discussed self-regulation in thesis writing course, especially in motivation (Mbato & Cendra, 2019). According to Mbato and Cendra (2019), motivation-regulation is a paramount aspect for students in thesis writing course as it helps the students to maintain their motivation as well as assist them to find help when it is needed. This topic is relevant to the educational context in Indonesia as writing a thesis is a requirement for the students to graduate.…”
Section: Introductionmentioning
confidence: 99%
“…They did not investigate as the major topic the assessment as learning in programs of teaching and learning English as a foreign language. Other researchers researched into the central component of the assessment as learning, that is, self-regulated learning, but they did not mention the assessment as learning in their research (Oz, 2014;Burner, 2015;Mican and Medina, 2015;Purwanti, 2015;Wei, 2015;Wang, 2016;Huang, 2016;Saefurrohman, 2017;Ahmed and Abouabdelkader, 2018;Dewi, Marlina, dan Supriyono, 2019;Mbato and Cendra, 2019;Zainuddin, Habiburrahim, Muluk, and Keumala, 2019;Cho, Yough, and Levesque-Bristol, 2020;Nawas, 2020). Moreover, levels of education in which those researches of the assessment as learning in programs of teaching and learning English as a second or foreign language took place are early education (Britton, 2015), elementary school (Lee, Mak, and Yuan, 2019;Tante, 2018), and high school (Saefurrohman, 2015;Lee, 2017), not higher education.…”
Section: Introductionmentioning
confidence: 99%